Effect of convective heat and mass conditions in magnetohydrodynamic boundary layer flow with joule heating and thermal radiation - Sharma, Ram Prakash; Tinker, Seema; Gireesha, B. J.; Nagaraja, B. (Zielona Góra: Uniwersytet Zielonogórski)
A free convection viscous MHD flow over a semi-infinite vertical sheet with convective heat and mass conditions has been considered. The effects of thermal radiation, chemical reaction and Joule heating on flow are also accounted. The governing nonlinear partial differential equations have been transformed into a set of highly non-linear coupled ordinary differential equations (ODEs) using appropriate similarity transformations.
Keywords: convection; MHD; Joule heating; chemical reaction; thermal radiation